Restorative Justice Approach To Victimless Crime - Toni Kasmiri; I Nyoman Nurjaya; Priya Djatmika (CV. AFDIFAL MAJU BERKAH, 2024)
Restorative Justice (RJ) involves the victim, perpetrator, victim/perpetrator's family and other parties that are resolved out of court. The parties, namely the perpetrator's family and the victim's family, agreed to resolve the problem by providing compensation. The crime of drug abuse has no victims or a victimless crime. Handling drug abuse, there is a common view and perception of law enforcers from the BNN, Police, Attorney General's Office and District Court, as victims and not criminals. In fact, there are still many law enforcement officials who treat drug users and abusers as criminals and not as victims. The existence of these differences in perception, makes the existence of confusion in handling using the RJ approach. The research uses normative juridical methods. The results of the research concluded that: There needs to be a guarantee of legal certainty in the handling of narcotics abusers, in the form of guidelines in the form of cooperation between the Supreme Court, the Attorney General's Office and the Police as law enforcers so that there is a common perception. The guidelines for handling narcotics abuse in handling RJ are expected to be a solution to the situation of prisons in Indonesia which are over capacity, with the rehabilitation of addicts expected to be free from dependence and for the community not to be restless.